The consequences of not having eosinophils. Issue 7 (6th June 2013) - Gleich, G. J.; Klion, A. D.; Lee, J. J.; Weller, P. F.
Abstract Several lines of evidence suggest that deficiency of eosinophils is not associated with any characteristic abnormality. Patients lacking eosinophils, in the setting of immunodeficiency or as a consequence of IgG‐mediated eosinophil precursor destruction, do not display any distinguishing abnormalities related to eosinophil reduction. The observation that eosinophil‐deficient mice do not display any distinctive syndrome or failure of their health is evidence that, under ordinary laboratory conditions, the eosinophil does not play a critical role in the well‐being of mammals. Observations that monoclonal antibodies to interleukin‐5 (IL‐5) are well tolerated appear unsurprising in light of these findings. For example, patients with the hypereosinophilic syndrome have received mepolizumab, an anti‐IL‐5 monoclonal antibody, for as long as 6 years and have not developed any characteristic set of adverse events. Safety data for reslizumab, another anti‐IL‐5 monoclonal antibody, and benralizumab, a monoclonal antibody to the IL‐5 receptor α‐chain, are comparatively limited, especially for benralizumab, although reports of administration of these antibodies to humans suggest that they are well tolerated. Thus, data to the present suggest that reduction of eosinophils appears to have no characteristic ill effects on normal health, and monoclonal antibodies that deplete eosinophils have the potential to be widely employed in the treatment of eosinophil‐associated diseases.